Digital studio vs. conventional in teaching architectural design process - Ismail, Mohd Arif; Mahmud, Rosnaini; Hassan, Isham Shah (Elsevier, 2012)
The main objective of this paper is to present an action research conducted in a polytechnic in determining the effect of using digital studio on architectural diploma students for teaching the design process compared to the use of conventional studio. For the past three years part of the semester six students had been exposed to the use of digital studio for the design process in helping students to produce creative design and more alternative ideas. The semester six students were selected for this study because all of these students already had basic skills to produce three- dimensional digital model using AutoCAD which they learn in semester five. The creativity of the design products for this study had been evaluated using an instrument developed based on the Creative Product Analysis Matrix (CPAM) (Besemer and Treffinger 1981). The strength of the design products was not affected by the quality of students’ drawing, but depended a lot on the characteristics of creative products that were based on CPAM model. Students were involved with the use of a digital studio in the design process using AutoCAD, SketchUp, 3D Studio Viz and Lumions. This study involved architectural students with 12 different design projects in the period of three years. For the research purposes students were divided into two groups, one group involved in design activities using digital studio and the other group involved in design activities using conventional method. In this study no new digital studio was built physically, but every student was involved with the use of a digital studio in the design process required to carry out design activities in CAD lab, or students were asked to use their laptop in the studio. This study shows that students from groups that used digital studio in the design process produce more alternative ideas. Study also shows the digital design method can produce more complex and dynamic design ideas.